Antarctica: the legal regime - Redgwell, C (Manchester University Press, 1990)
Reviews various elements of the region's legal regime, beginning with the 1959 Antarctic Treaty and its subsequent modifications, considering also the Sealing Convention, the Marine Living Resources Convention, and the 1988 Convention on the Regulation of Antarctic Mineral Resource Activities. The paper describes proposals for change from France, Australia, New Zealand, the US, Chile, and Sweden, and discusses possible means of progress. The author hopes to assist this process by examining the jurisdictional provisions of the existing Antarctic Treaty framework, and the extent to which the proponents of change have addressed this issue. -P.Hardiman